Using Implementation Mapping to Build Organizational Readiness - Amber K. Watson; Belinda F. Hernandez; Jenny Kolodny-Goetz; Timothy J. Walker; Andrea Lamont; Pam Imm; Abraham Wandersman; Maria E. Fernandez (Frontiers Media S.A., 2022)
Organizational readiness is essential for high-quality implementation of innovations (programs, policies, practices, or processes). The R = MC2 heuristic describes three readiness components necessary for implementation-the general functioning of the organization (general capacities), the ability to deliver a particular innovation (innovation-specific capacities), and the motivation to implement the innovation. In this article, we describe how we used the Readiness Building System (RBS) for assessing, prioritizing, and improving readiness and Implementation Mapping (IM), a systematic process for planning implementation strategies, to build organizational readiness for implementation of sexual assault prevention evidence-based interventions (EBIs). While RBS provides an overarching approach for assessing and prioritizing readiness constructs (according to the R = MC2 heuristic; Readiness = Motivation x general Capacity × innovation specific Capacity), it does not provide specific guidance on the development and/or selection and tailoring of strategies to improve readiness. We used the five IM tasks to identify and prioritize specific readiness goals and develop readiness-building strategies to improve subcomponents described in the R = MC2 heuristic. This article illustrates how IM can be used synergistically with the RBS in applied contexts to plan implementation strategies that will improve organizational readiness and implementation outcomes. Specifically, we provide an example of using these two frameworks as part of the process of building organizational readiness for implementation of sexual assault prevention EBIs.